Factors inhibiting effective risk management in emerging market SMEs - Oscar Chakabva; Robertson Khan Tengeh; Job Dubihlela (Journal of Risk and Financial Management, 2021)
Despite the anecdotal evidence that suggests that SMEs adopt inadequate and ineffective risk management practices, only a few studies have been conducted on the topic in the emerging market context. Besides, the existing studies on factors inhibiting effective risk management in emerging market SMEs are devoid of any theoretical grounding. This situation implies that there is still a knowledge gap on this area, and this gap is what the current paper seeks to close. In closing out the gap, this paper used the Resource Based View theory to interpret the results obtained, in order to help clarify the factors inhibiting effective risk management in emerging market SMEs, with a case of South Africa being used. In a first step, questionnaires were distributed to a sample of 320 FMCG SMEs in the Cape Metropolitan area. The results revealed the significance of both intangible and tangible resources in positively impacting the effectiveness of risk management within SMEs. This led to the conclusion that owner-managers must pay particular attention to their intangible and tangible resource structure, which will impact the positive response towards superior performance and competitive advantage by focusing more on coalescing resources that lead to effective risk management.
Keywords: 330; emerging markets; FMCG SMEs; risk management; South Africa